Model to Information System Management on Educational Quality Assurance of Bureau Educational Testing, Office of Basic Education Commission: - Inkongngam, Anongnart; Sikkhabandit , Sowwanee; Theerawitthayalert, Panya (Interdisciplinary Academic and Research Journal, 2023)
The Ministry of Education has recognized the importance of educational information as information systems will help to support executive decision-making, each executive will make different decisions based on experience, knowledge, intelligence, way of thinking, and many other factors. Information is another important factor in supporting executives to make more efficient decisions. The objectives of this research were: (1) To study the conditions and guidelines for information system management for basic education quality assurance of the Bureau of Educational Testing. Office of the Basic Education Commission. (2) to create an information system management model for basic education quality assurance of the Bureau of Educational Testing Office of the Basic Education Commission. (3) to assess the model of information system management on educational quality assurance. Education Executives and school directors or teachers responsible for quality assurance, totaling 247 people in total, 12 informants. Tools used in the research. These were questionnaires, interview forms, and statistics used in the research were mean and standard deviation. and content analysis. The research findings were as follows: (1) Information system management for basic education quality assurance of the Bureau of Educational Testing. Office of the Basic Education Commission Overall, it was at a high level. and information system management guidelines for basic education quality assurance It corresponds to the elements of the 3-element model as follows: Component 1 Management consists of 1) Planning 2) Organization 3) Leading and 4) Controlling 2nd component Information system management consists of 1) data collection 2) data audit 3) data processing 4) data analysis 5) data utilization and 6) data warehousing. Component 3: Quality Cycle Management (PDCA) consists of 1) Planning (Plan) 2) Implementation (Do) 3) Check (Check) and 4) Correction (Act). (2) The Office of the Basic Education Commission found that the information system management model for basic education quality assurance of the Bureau of Educational Testing the Office of the Basic Education Commission consists of 4components: administration; information system administration. (3) Assessment of information system management model for basic education quality assurance of the Bureau of Educational Testing. Office of the Basic Education Commission Assessment Results Accuracy Appropriateness Possibility and overall usefulness were at a high level.